Current role of chimneys and sandwich grafts in complex aneurysm repair. (August 2012) - Kolvenbach, Ralf R; Karmeli, Ron; Bachar-Rubinstein, Adi
Parallel grafts are an emerging alternative to open surgery in complex aneurysm repair. In most cases up until now custom-made devices can be used in many instances yet are associated with considerable manufacturing times and costs. Chimney techniques can offer an off-the-shelf solution. We distinguish between plain chimney grafts to maintain perfusion of side branches like the renal arteries and more complex repair techniques to treat thoracoabdominal aortic aneurysms with sandwich grafts. Indications and different deployment techniques of various configurations, such as periscope grafts, are described. Chimney grafts can either be used as a bailout after accidental covering of a renal artery, or as a side branch running in parallel to an aortic graft. Midterm results and multicenter studies are discussed in the manuscript. Sandwich grafts offer a readily available solution in thoracoabdominal aortic aneurysms. Here the branches and the gutters are between two aortic stent grafts rather than between the native aorta and the aortic stent. This further stabilizes the branches reducing friction. Persicope grafts can replace upward-facing chimney grafts in those cases where a narrow aorta does not permit placement of four branches or where a two-team approach is favored to save time. These techniques can be used not only in suprarenal and thoracoabdominal pathology but also in aortic arch aneurysms. There are only a few studies so far with midterm results equal to the mid- and long-term results of custom-made branched and fenestrated devices. This review outlines alternative techniques for complex aneurysm repair. Although they are technically feasible with low morbidity and mortality, robust data supporting their use are lacking. Long-term durability and target vessel patency are still to be determined. Challenges, particularly in the aortic arch and in thoracoabdominal aortic aneurysms, currently make parallel grafts an attractive alternative to other endovascular techniques or open surgical procedures. Yet since there is a lack of long-term data we do not know whether these off-the-shelf techniques are only a step in between until premanufactured off-the-shelf devices become more widely applicable.